Hiperglicemia induz a O-glicosilação com N-acetilglucosamina no fator de transcrição NF-κB e aumenta a produção de citocinas em placentas de ratas - Justina, Vanessa Dela (2017)
Activation of NF-κB may result from the classical (canonical) pathway, with disconnection of the IκB inhibitor and subsequent nuclear translocation or, alternatively, by post-translational modifications via O-linked with N-acetylglucosamine (O-GlcNAc) on the p65 subunit of NF-κB (non-canonical pathway). This modification is directly controlled by two enzymes activity: OGlcNAc transferase (OGT), responsible for catalysis and O-GlcNAcase (OGA), performs the hydrolytic removal. We hypothesized that hyperglycemia-induced increased O-GlcNAc in transcription factor NF-κB in placental tissue, leading to augmented production of proinflammatory cytokines, culminating in placental dysfunction and fetal restriction growth. Single injections of streptozotocin (40 mg/kg, i.p.) or vehicle were used to induce hyperglycemia or normoglycemia, respectively, in female Wistar rats (12-14 weeks). After three days, rats were mated and pregnancy confirmed by vaginal smear. Placental tissue was collected at 21 days of pregnancy. Placental expression of p65 subunit was similar between groups. However, nuclear translocation of p65 subunit (p= 0.0461), showing greater activation of NF-κB, was increased in the hyperglycemic group. Reduced expression of IκB (p= 0.002) and increased expression of phosphorylated IκBSer32 (p= 0.038) were observed in hyperglycemic placentas, demonstrating increased classical NF-κB activation. Augmented modification of O-GlcNAc-modified proteins (p= 0.033) was found in hyperglycemic placentas and p65 subunit was a key O-GlcNAc target, as demonstrated by immunoprecipitation (p= 0.034). Analyzing the enzymes involved in the O-GlcNAc modification, a decrease in OGA (p= 0.0312) was observed in the placental tissue of hyperglycemic rats, while the expression of OGT and GFAT (Glutamine: fructose-6-phosphate aminotransferase) enzymes did not change between the groups. Tumor necrosis factor-alpha [(TNF-α); p= 0.034] and interleukin-6 [(IL-6); p= 0.002] expressions were increased in hyperglycemic placentas. Furthermore, placental weight was increased, whereas fetal weight, number of fetuses, gestational weight gain and placental efficiency were decreased under hyperglycemic conditions. TNF-α and IL-6 demonstrated positive correlations with placental weight and negative correlations with fetal weight, number of fetuses, gestational weight gain and placental efficiency. Therefore, under hyperglycemic conditions, a modulatory role of OGlcNAc in NF-κB activity was demonstrated in placental tissue, contributing to fetal and placental dysfunction due to inflammatory cytokines exacerbation.